The Role of Membranes and Lipid-Protein Interactions in the Mg-Branch of Tetrapyrrole Biosynthesis - Solymosi, Katalin; Mysliwa-Kurdziel, Beata (Frontiers in Plant Science, 2021)
Chlorophyll (Chl) is essential for photosynthesis and needs to be produced throughout the whole plant life, especially under changing light intensity and stress conditions which may result in the destruction and elimination of these pigments. All steps of the Mg-branch of tetrapyrrole biosynthesis leading to Chl formation are carried out by enzymes associated with plastid membranes. Still the significance of these protein-membrane and protein-lipid interactions in Chl synthesis and chloroplast differentiation are not very well understood. In this review, we provide an overview on Chl biosynthesis in angiosperms with emphasis on its association with membranes and lipids. Moreover, the last steps of the pathway including the reduction of protochlorophyllide (Pchlide) to chlorophyllide (Chlide), the biosynthesis of the isoprenoid phytyl moiety and the esterification of Chlide are also summarized. The unique biochemical and photophysical properties of the light-dependent NADPH:protochlorophyllide oxidoreductase (LPOR) enzyme catalyzing Pchlide photoreduction and located to peculiar tubuloreticular prolamellar body (PLB) membranes of light-deprived tissues of angiosperms and to envelope membranes, as well as to thylakoids are also reviewed. Data about the factors influencing tubuloreticular membrane formation within cells, the spectroscopic properties and the in vitro reconstitution of the native LPOR enzyme complexes are also critically discussed.